Impairment of cognitive function in ornithine transcarbamylase deficiency is global rather than domain-specific and is associated with disease onset, sex, maximum ammonium, and number of hyperammonemic events - Bürger, Corinna; Garbade, Sven; Kölker, Stefan; Burgard, Peter (Journal of inherited metabolic disease, 2019)
Beginning in 2006, the Urea Cycle Disorders Consortium (UCDC) has conducted a longitudinal study of eight inherited deficiencies of enzymes and transporters of the urea cycle, including 444 individuals with ornithine transcarbamylase deficiency (OTCD), of whom 300 (67 males, 233 females) received psychological evaluation. In a cross-sectional study (age range, 3-71 years), analysis of covariance (ANCOVA) determined the association between outcomes in five cognitive domains (global intelligence, executive functions, memory, visuomotor integration, visual perception) and sex, age at testing and timing of disease onset defined as early onset (≤28 days; EO), late onset (LO), or asymptomatic (AS). The dataset of 183 subjects with complete datasets (31 males, 152 females) revealed underrepresentation of EO subjects (2 males, 4 females), who were excluded from the ANCOVA. Although mean scores of LO and AS individuals were within 1 SD of the population norm, AS subjects attained significantly higher scores than LO subjects and males higher scores than females. Correlations between cognitive domains were high, particularly intelligence proved to be a distinguished indicator for cognitive functioning. Maximum plasma ammonium concentration and intelligence correlated significantly higher in EO (r = −0.47) than in LO subjects (r = 0.04). Correlation between the number of hyperammonemic events and intelligence scores were similar for EO (r = −0.30) and LO (r = −0.26) individuals. The number of clinical symptoms was significantly associated with intelligence (r = −0.28) but not with scores in other domains. Results suggest that OTCD has a global impact on cognitive functioning rather than a specific effect on distinct cognitive domains.
First published: 27 December 2018
Gesehen am 09.05.2019